The Effect of Using Cooperative Learning on Achievement in Football - Salem Al Qarra (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims to identify the effect of using cooperative learning on  achievement of students studying football in School of Physical Education at the University of Jordan. The researcher used a quasi-experimental method. The sample of the study consisted of (39) male and female students from Football Course (2). Two sections were chosen in an intentional method: the first section as a control group and it consisted of (14) female students and (6) male students who learned in a traditional method, and the second section as an experimental group and it consisted of (9) female and (10) male students who learned by a cooperative strategy. The results of the study showed a positive effect of the traditional teaching method and the cooperative learning strategy on improving skill performance for males and females. The researcher recommends diversifying teaching strategies during the lecture, especially including a cooperative learning strategy in teaching football skills.